E-Book Development To Improve Spatial Literacy In Elementary Geometry Learning - Rahma Nadhira Putri; Nurafni Nurafni (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2025)
The low level of spatial literacy among elementary school students in geometry is one of the main challenges in mathematics education. This issue is largely due to the lack of interactive learning media and the limited use of instructional methods that support spatial understanding. This study aims to develop a multimedia-based interactive e-book on plane geometry to ence the spatial literacy of fifth-grade students. The research employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Debelopment, Implementation, Evaluation). The participants were 32 Fifth-grade students from SDN Kebon Jeruk 08, West Jakarta. Resesrch instruments included observaitions, interviews, expert validation questionnaires, and pre-test and post-test assessment. The validation results indicated that the interactive e-book is feasible for use, with a feasibility score of 94%. The effectiveness test showed a significant improvement in students’ spatial literacy, with a t-test revealing a mean difference of 26.48 points (p<0.001) between the pre-test and post-test scores. Students became more active, motivated, and cable of communicating spatial ideas more effectively. Therefore, the interactive e-book has proven to be an effective innovarive learning medium for improving elementary students’ spatial literacy. This study recommends the integration of e-books into geometry instruction and teacher training programs to optimize the use of digital media in the classroom.